Routledge handbook on Zionism
1 online resource
Keywords: "This Handbook, the first of its kind, provides an in-depth examination of the evolution, ideology, history and culture of Zionism and its various movements. Distancing itself from the slogans and cliches of advocacy, the volume provides much-needed context and background on the emergence of Zionism. The Handbook is divided into eight parts - with contributions from some forty of the world's leading scholars on Zionism - to elucidate its various strands. These include underrepresented areas such as Zionism in the Arab World before the establishment of the state of Israel, Zionism and Marxism, the emergence of the Zionist Right, the language war between Hebrew and Yiddish, the struggle for Jewish women's suffrage, the poetry of Lea Goldberg, and Zionism in emerging new Jewish communities in locations like Papua New Guinea, Guatemala and Zimbabwe. Another section on Zionism in repressive states stretches from an examination of Zionism in Hitler's Germany to the Ayatollahs' Iran today; from subterranean Zionism in Stalin's Russia to apartheid South Africa. The volume concludes by examining current issues, including the relationship between evangelicals and Zionism in the US, and the representation of Zionism in the age of the internet. Providing a sweeping overview of Zionism in its many forms, the volume will appeal to students, researchers and general readers interested in Jewish studies in the Middle East and beyond, as well as those seeking to understand the roots of contemporary Israel"--